2022
DOI: 10.3389/fpls.2022.967352
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Myrothamnus flabellifolia MfWRKY41 confers drought and salinity tolerance by enhancing root system and antioxidation ability in Arabidopsis

Abstract: Myrothamnus flabellifolia is the only woody resurrection plant discovered so far and could recover from extreme desiccation condition. However, few genes related to its strong drought tolerance have been characterized, and the underlying molecular mechanisms remains mysterious. Members of WRKY transcription factor family are effective in regulating abiotic stress responses or tolerance in various plants. An early dehydration-induced gene encoding a WRKY transcription factor namely MfWRKY41 was isolated from M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Furthermore, PtoWAK106 was found to increase the stability of the PtoE2Fa‐PtoDPb1 complex (Figure 6e–j ). We also identified the up‐regulation of several drought‐resistance‐related genes, such as WRKY40 , NAC72 , and ERF5 , in PtoDPb1 ‐OE plants (Huang et al ., 2022 ; Li et al ., 2022 ; Yao et al ., 2021 ). It is therefore plausible to hypothesize that the expression of PtoWAK106 is induced by drought, which then modulates the function of PtoDPb1 and its downstream signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PtoWAK106 was found to increase the stability of the PtoE2Fa‐PtoDPb1 complex (Figure 6e–j ). We also identified the up‐regulation of several drought‐resistance‐related genes, such as WRKY40 , NAC72 , and ERF5 , in PtoDPb1 ‐OE plants (Huang et al ., 2022 ; Li et al ., 2022 ; Yao et al ., 2021 ). It is therefore plausible to hypothesize that the expression of PtoWAK106 is induced by drought, which then modulates the function of PtoDPb1 and its downstream signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The leaves were floated on a stomatal opening solution (10 mM KCl, 0.2 mM CaCl 2 , and 10 mM MES-KOH; pH, 6.15) for 2.5 h to induce stomatal opening. Then, the lower epidermis of leaves was placed in an opening solution with 7.5% PEG6000 and treated in a growth incubator for 2.5 h [ 60 ]. The stomata were observed and photographed using a microscope, and the width and length of 50 stomata per line were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Recent transcriptome studies have shown that herbaceous plants, such as wheat (Triticum aestivum L.) [33], licorice (Glycyrrhiza glabra L.) [34], broad bean (Vicia faba L.) [35], and millet (Panicum miliaceum) [36] upregulate WRKY TFs in response to drought stress. WRKY TFs in various woody plants, including Myrothamnus flabellifolia [37], and oil palm (Elaeis guineensis Jacq.) [38], also respond to drought stress.…”
Section: Introductionmentioning
confidence: 99%